The pregnancy experiences and antenatal care services of Chinese migrants in Switzerland: a qualitative study - Dingcui Cai; Paulina Villanueva; Susannah Stuijfzand; Hong Lu; Basile Zimmermann; Antje Horsch (BMC, 2022)
Abstract Background Differences in reproductive health outcomes according to the mothers' origins have been reported in Switzerland, for example, women from European countries and non-European countries. The Swiss Federal Office of Public Health has therefore called for specific Swiss-wide studies on migrant populations. This study explores the pregnancy and antenatal care experiences of Chinese migrants in Switzerland, intending to clarify their maternity care needs. Methods In-depth interviews of 14 Chinese mothers and 13 family members were conducted in Chinese or English and audio recorded. All audio-recordings were transcribed verbatim. All Chinese transcripts were translated into English. Thematic analysis was performed with the assistance of the qualitative data analysis software, MAXQDA Analytics Pro 2020. Results Five themes were extracted from the transcripts: (1) Motivations and concerns about having children, (2) The merits of the Swiss maternity care system, (3) The inconveniences and barriers of accessing Swiss maternity care services, (4) Strategies to deal with the inconveniences of the Swiss maternity care system, and (5) The need for culturally sensitive care. Conclusions The results of our study provide new knowledge and understanding of pregnancy experiences and antenatal care services of Chinese mothers and their families in Switzerland. Their unique positive experiences included: family planning, the continuity of maternity services, humane care with the privacy respected, personalized sensitive care needs, preferences for female obstetricians and obstetricians of Asian origin. Several barriers were highlighted, such as information seeking difficulties, communication difficulties, and a rigid appointment system. Reducing barriers enabling access to maternity care services within the Swiss healthcare system is necessary to provide equal quality maternity care for individuals, irrespective of their origins.